Job Embeddedness and Work Performance : A Systematic Review and Meta-Analysis - Vashisht, Ravi; Kaushal, Poonam; Vashisht, Sakshi (Prabandhan: Indian Journal of Management, 2022)
The present study employed systematic review and meta-analytic techniques to examine the literature on job embeddedness and work performance. Work performance was measured in terms of discretionary behaviors (i.e., organizational citizenship behavior and counterproductive workplace deviance) and non-discretionary behaviors (i.e., task performance). Product – moment correlation coefficient (r) was the effect size for this study. From the results of 37 studies, statistically significant meta-analytic correlation was found between job embeddedness and organizational citizenship behavior and task performance. No relationship was found between job embeddedness and counterproductive workplace behavior. For heterogeneity, sub-group analysis was conducted. Implications, potential limitations, and future directions were also discussed.